On the Positive Effects of Overcon fident Self-Perception in Teams - Sandra Ludwig; Philip C. Wichardt; Hanke Wickhorst (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2011)
In this paper, we study the individual payoff effects of overconfident self-perception in teams. In particular, we demonstrate that the welfare of an overconfident agent in a team of one rational and one overconfident agent or a team of two overconfident agents can be higher than that of the members of a team of two rational agents. This result holds irrespective of the assumption about the agents' awareness of their colleague's bias. Moreover, we show that an overcondent agent is always better of when he is unaware of a potential bias of his colleague.
urn:nbn:de:bvb:19-epub-12246-0
Keywords: D21; D62; L23; 330; Overconfidence; Team Production; Arbeitsgruppe; Vertrauen; Persönlichkeitspsychologie; Leistungsmotivation; Wohlfahrtsanalyse; Theorie